PENGARUH PENDIDIKAN KEWARGANEGARAAN DALAM MEMBANGUN KARAKTER GENERASI MUDA - Vandita, Lalu Yoga; Taufik, Ahmad (LPPM Institut Pendidikan Nusantara Global, 2023)
Citizenship education is an educational process to build exemplary will and ability to develop creativity that reflects national identity which is conditional on Indonesian socio-cultural values. Citizenship Education (Civic Education) which places proportional aspects of Education. The basis of the research used to obtain the results of the influence of civics education on the younger generation is by means of a survey. The survey aims to collect information about variables from a population or group of objects. This research is widely used to solve problems in the field of education including policy formulation. Based on the survey results percentage chart, we can draw a conclusion if the younger generation has implemented religious character, democratic character, discipline, responsibility, critical thinking, and caring for others.